2014
DOI: 10.1109/tmtt.2014.2359647
|View full text |Cite
|
Sign up to set email alerts
|

A Digital Interpretation of Frequency-Periodic Signal-Interference Microwave Passive Filters

Abstract: This paper addresses, for the first time, the digital representation of spectrally periodic signal-interference microwave passive filters. Starting from the theoretical rational transfer function of a synthesized transmission-line signal-interference analog filter, the real-valued coefficients of its digital-domain filter counterpart are derived. This discrete-time formulation for this type of microwave filters allows to clarify some confusing concepts into them, such as filter order. Moreover, some particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
0
19
1
Order By: Relevance
“…The periodicity in frequency for these filters comes from the fact that they are usually composed of transmission-line segments with electrical lengths related by integer numbers, whose spectral behaviour is mathematically expressed by periodic trigonometric functions. On the other hand, given the periodicity of the frequency response -even-type symmetry for the amplitude response and odd-type symmetry for the phase response -of discrete-time linear time-invariant systems described by difference equations [19], it is possible to match an associated discrete-time counterpart with the aforementioned parameter S 21 f after noting that it can be written as follows [15]:…”
Section: Digital Modelling Of Losses In Frequencyperiodic Microwave Pmentioning
confidence: 99%
See 1 more Smart Citation
“…The periodicity in frequency for these filters comes from the fact that they are usually composed of transmission-line segments with electrical lengths related by integer numbers, whose spectral behaviour is mathematically expressed by periodic trigonometric functions. On the other hand, given the periodicity of the frequency response -even-type symmetry for the amplitude response and odd-type symmetry for the phase response -of discrete-time linear time-invariant systems described by difference equations [19], it is possible to match an associated discrete-time counterpart with the aforementioned parameter S 21 f after noting that it can be written as follows [15]:…”
Section: Digital Modelling Of Losses In Frequencyperiodic Microwave Pmentioning
confidence: 99%
“…As discussed in [15,16], the ideally synthesised power transmission response of a frequency-periodic microwave passive filter can be matched with the frequency response of an associated digital system. Thus, the coefficients a k and b k of the associated difference equation of the linear time-invariant discrete-time system can be extracted and the zero-pole diagram in the z-plane can be analysed.…”
Section: Introductionmentioning
confidence: 99%
“…As it was mentioned in the introductory section, a frequency-periodic microwave passive circuit is understood as an analogue passive device whose response can be matched to that of a digital LTI system with real-valued coefficients a k and b k . In particular, the ideal synthesised scattering-parameter-type response S ij ( f ) of this microwave passive circuit, where i and j refer to any two ports or even to the same one, can be formulated as follows [10]…”
Section: Research Articlementioning
confidence: 99%
“…One must analyse the frequency-periodic ideally-synthesised microwave structure as a function of the complex-valued variable zpreferably by making use of computer-based symbolic calculusand then write down the coefficients. The authors have recently applied this procedure to signal-interference microwave passive filters [10]. The study in [10] also revealed the existence of zero-pole cancelations (ZPCs) in the z-plane for these circuits, which enabledfor the first timethe explanation of spurious resonances observed in the measurements of some proof-of-concept prototypes of signal-interference microwave filters reported in the past [10].…”
Section: Introductionmentioning
confidence: 97%
“…Either the concept of filter order or the principle of generation of TZs seems to be ambiguous especially in the case of BSFs based on cross coupling or signal interference techniques. Thus, many researchers have paid their attention to such matters and tried to clarify a signal-interference BSF from the viewpoint of digital filters [15].…”
Section: Introductionmentioning
confidence: 99%